2023
DOI: 10.1097/gme.0000000000002215
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol levels and the risk of brain natriuretic peptide–diagnosed heart failure in postmenopausal women: a population-based prospective cohort study

Abstract: Objective Hormonal changes during menopause can disturb serum cholesterol which is closely associated with cardiovascular disease. This study investigated the prospective association between serum cholesterol and heart failure (HF) risk in postmenopausal women. Methods We analyzed data from 1,307 Japanese women, aged 55 to 94 years. All women had no history of HF, and their baseline brain natriuretic peptide (BNP) levels were less than 100 pg/mL. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A retrospective study conducted by Halldin showed that TC was not associated with the risk of HF later in life in 50-year-old women [ 40 ]. In contrast, another retrospective study showed that TC ≥ 240 mg/dL was positively associated with the risk of HF in postmenopausal Japanese women (HR = 1.70,95%CI, 1.04–2.77) [ 41 ]. In addition, a prospective cohort study showed that TC > 200 mg/dL in nondiabetic patients with chronic HF was associated with a 64% reduction in the 5-year risk of death [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted by Halldin showed that TC was not associated with the risk of HF later in life in 50-year-old women [ 40 ]. In contrast, another retrospective study showed that TC ≥ 240 mg/dL was positively associated with the risk of HF in postmenopausal Japanese women (HR = 1.70,95%CI, 1.04–2.77) [ 41 ]. In addition, a prospective cohort study showed that TC > 200 mg/dL in nondiabetic patients with chronic HF was associated with a 64% reduction in the 5-year risk of death [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, changes in certain cancer biomarkers during chemotherapy can reflect the tumor's response to treatment [ 52 ]. Additionally, biomarker levels can be used to predict disease prognosis, such as the level of BNP (brain natriuretic peptide) in the blood of cardiovascular disease patients being related to the risk of heart failure [ 53 , 54 ]. With the development of personalized medicine, the role of biomarkers in formulating personalized treatment plans is becoming increasingly prominent.…”
Section: Application Of Biobanks In Chronic Disease Researchmentioning
confidence: 99%